The Dorso-Lateral Flap in Post Burn Flexion Contracture of Fingers - A. K. Singh; G. S. Kalra; S. D. Pandey (Indian Journal of Plastic Surgery)
Volar defects of the fingers can be resurfaced by a flap from the dorso-radial or dorso-ulnar aspect of the same finger. Its use following release of twenty-one post burn flexion contracture of the fingers in fifteen patients has been discussed.